Effect of introduction of a standardized protocol in dispatcher-assisted cardiopulmonary resuscitation - Plodr, Michal; Truhlar, Anatolij; Krencikova, Jaroslava; Praunova, Monika; Svaba, Vladimir; Masek, Jiri; Bejrova, Dana; Paral, Jiri (Resuscitation, 2016)
BACKGROUND: The two most commonly used dispatch tools are medical priority dispatch (MPD) and criteria based dispatch (CBD), but there are countries still using non-standardized emergency call processing. We compared selected characteristics of DA-CPR before and after implementation of a standardized protocol in a non-MPD and non-CBD system. METHODS: Observational study of DA-CPR recordings during 4-month periods before (PER1) and after (PER2) the standardized protocol had been implemented. Selected performance characteristics included times to event verification, identification of cardiac arrest, DA-CPR instructions, and first chest compression, which were compared between PER1 and PER2. The secondary goal was to compare survival to hospital discharge. RESULTS: A total of 152 call recordings with DA-CPR were evaluated in PER1 and 174 in PER2. Median times to cardiac arrest recognition were 46s in PER1 and 37s in PER2 (p=0.002), to first compression 2min 35s in PER1 and 2min 25s in PER2 (p=0.549). Admission to hospital with return of spontaneous circulation (ROSC) was achieved in 39 patients (31.9%) in PER1 and 57 (45.6%) in PER2 (p<0.05), discharge from hospital (CPC 1-2) in 9.0% and 14.4% patients in PER1 and PER2, respectively. If ventricular fibrillation was the initial rhythm, survival rate (CPC 1-2) was 32.3% in PER1 and 38.7% in PER2 (p=0.523). CONCLUSION: Implementation of a standardized DA-CPR protocol resulted in faster identification of cardiac arrest, response team dispatching and arrival at scene. These factors were associated with a trend to better survival.
Keywords: Out-of-hospital cardiac arrest; Humans; Dispatcher-assisted cardiopulmonary resuscitation; lidé středního věku; Cardiopulmonary Resuscitation; Emergency Medical Service Communication Systems; Female; Aged; terapie náhlých příhod; Emergency Treatment; senioři; lidé; kardiopulmonální resuscitace; časové faktory; komunikační systémy urgentních lékařských služeb; ženské pohlaví; Male; Middle Aged; Retrospective Studies; Czech Republic; zástava srdce mimo nemocnici; Out-of-Hospital Cardiac Arrest; retrospektivní studie; Česká republika; mužské pohlaví; Time Factors; Emergency medical dispatch centre; Telephone; telefon